The next steps for expanding and developing sport biomechanics - Ae, M. (Sports Biomechanics, 2020)
This paper reviews a series of sport biomechanics research projects with long-term support of the Japan Association of Athletic Federations (JAAF) on the feedback loop of sport biomechanics. The JAAF supported these studies focusing on providing feedback to athletes and coaches based on biomechanical data. The primary topics of discussion are the standard motion model for teaching and coaching, inter-individual motion variation and deviation, and classification of athletes' motions. Additionally, a comment is presented on motion-decision criterion, or objective function for body segment recruitment with examples of running and jumping. This paper concludes with remarks on how to expand the research in sport biomechanics and how to bridge the gap between researchers and practitioners. It is advisable for sport biomechanists to further explore biomechanical principles of human movement from the viewpoint of sports, to mutually understand features of research and practice sides and to be more involved in performance analysis and improvement in sports techniques.